Experimental and statistical analysis of vegetable oil-brine egg yolk emulsion quench on the properties of AISI 4140 steel. Issue 1 (31st December 2022) - Passanha, Joel; Sharma, Sathyashankara; Hegde, Ananda; Lakshmi, Bhagya; Shankar, Gowri; Murthy, Guru
Abstract: In the current study, AISI 4140 steel is subjected to quenching treatment using different oils and quenchants with varying conditions. In this study, emulsions of Coconut, Karanja and Pinnay oil and Brine in different ratios are prepared with and without egg yolk as the emulsifier. The mechanical properties of steel specimens quenched in these emulsions are tested experimentally, analysed statistically and results are validated. Regressions equations are fit to determine the hardness and impact energy of the samples quenched at different conditions. Response Surface Methodology optimization tool is used to obtain the optimized values for viscosity and cooling rate of the solution to obtain the superior combination of hardness and impact energy. Improvement is the hardness is observed for the samples quenched with the emulsions of coconut oil and brine with lower vol% of oil due to their lower viscosity and higher cooling rate.